Peran Pendidikan Kristen dalam Menjawab Krisis Moral Anak Bangsa - Oferlin Hia (Sekolah Tinggi Teologi SAPPI Ciranjang, 2025)
This article examines the role of Christian education in shaping faith, character, and moral integrity among Indonesian youth amid the nation’s ongoing moral crisis. Responding to increasing violence, ethical degradation, and the erosion of human values, Christian education is explored as both a theological and pedagogical response. This study employs a qualitative approach through a literature review of theological, educational, and relevant scholarly sources. The findings indicate that Christian education functions as a transformative agent when implemented integratively through family, church, schools, and higher education institutions. Beyond the transmission of religious knowledge, Christian education emphasizes character formation rooted in values of love, justice, integrity, and social responsibility. Within Indonesia’s pluralistic society, Christian education is challenged to remain contextual, dialogical, and inclusive while faithfully maintaining its Christian identity.